2018
DOI: 10.4102/phcfm.v10i1.1471
|View full text |Cite
|
Sign up to set email alerts
|

Husbands’ participation in birth preparedness and complication readiness and associated factors in Wolaita Sodo town, Southern Ethiopia

Abstract: BackgroundThe poor emphasis on the role of husbands in birth preparedness and complication readiness (BPCR) is a major factor that should be addressed in tackling maternal mortality.AimTo assess the level of husbands’ participation in BPCR and associated factors.SettingWolaita Sodo town, Southern Ethiopia.MethodsA community based cross-sectional study was conducted among 608 husbands of pregnant women and nursing mothers. Multivariate logistic regression model was used for the analysis.ResultsForty-five per ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
38
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 34 publications
10
38
2
3
Order By: Relevance
“…12 A study in North Ethiopia, found that majority of husbands were aware of components of BPCR such as identifying transport (65.4%), identifying place of delivery (62.2%) and saving money for delivery (76.3%), while only few identified a blood donor in advance (17.3%), which was also found in a study in South Ethiopia. 9,13 The proportion of husbands aware of the individual components of BPCR match those of our study, except for identifying transport in advance, which was higher in our study. This could be due to the socioeconomic difference in the two populations, where the present study population, though rural, has access to their own private vehicles as transport, and therefore did not actually have to make additional specific emergency transport arrangements, as was the case in rural Bhadohi district of Uttar Pradesh.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…12 A study in North Ethiopia, found that majority of husbands were aware of components of BPCR such as identifying transport (65.4%), identifying place of delivery (62.2%) and saving money for delivery (76.3%), while only few identified a blood donor in advance (17.3%), which was also found in a study in South Ethiopia. 9,13 The proportion of husbands aware of the individual components of BPCR match those of our study, except for identifying transport in advance, which was higher in our study. This could be due to the socioeconomic difference in the two populations, where the present study population, though rural, has access to their own private vehicles as transport, and therefore did not actually have to make additional specific emergency transport arrangements, as was the case in rural Bhadohi district of Uttar Pradesh.…”
Section: Discussionsupporting
confidence: 75%
“…When comparing the use of mass media and technology in preparing for birth, in South Ethiopia about half of the husbands in the study (51.4%) had heard about BPCR from the radio, 43.9% from television and 28.0% from newspapers. 13 However, in our study, the most common source of information regarding birth preparedness was found to be mobile phones (30.8%) and much lower proportion used newspaper (21.1%), television (14.3%) and radio (14.3%) as sources of information on BPCR. This is due to the widespread rural penetration of mobile phones and the availability, and affordability of smart phones.…”
Section: Discussioncontrasting
confidence: 56%
“…In sub-Saharan Africa, husband antenatal care attendance varies between 12.5%-18.7% [17] and in Ethiopia studies showed that husband antenatal care attendance is rage from 19.7 22.7% [18][19][20]. Husband ANC attendance program still remains low in developing countries including Ethiopia [11][12][13]. Recent studies on the topic suggest that there were a number of reasons for low level of husband antenatal care attendance which include cultural barriersand norms, knowledge on ANC, sociodemographic characteristics, male individual opinions and health system barriers [21][22][23][24] According to the EDHS 2016 report only 62% of women have at least one antenatal care visit nationally and 67% of women have at least one antenatal care visit in Amhara region where the study area belongs [25].…”
Section: Introductionmentioning
confidence: 99%
“…The total sample size of the included studies in this review were 4210, ranging among studies included from 125 in Nepal [42] to 592 in Ethiopia [43]. Five of the included studies were from Asia [10,42,[44][45][46], seven studies from Africa with the majority from Ethiopia [43,[47][48][49][50][51][52]. Additionally, all studies included in the review were cross-sectional study designs (Table 1).…”
Section: Study Inclusionmentioning
confidence: 99%